Peran Organisasi Kemasyarakatan Pemuda Muhammadiyah Dalam Pencegahan Prostitusi Terselubung di Kecamatan Medan Belawan - Fitri Yani; Muhammad Ihsan (Universitas Medan Area, 2020)
In Medan Belawan sub-district, disguised prostitution often occurs in the community with many boarding houses turned into prostitution places. This study aims to analyze the forms of prostitution undercover boarding houses that occur in Medan Belawan District and the role of the Muhammadiyah Youth Organization in preventing hidden prostitution of boarding houses in Medan Belawan District. By using the empirical juridical research method, namely conducting direct interviews with the Branch Leaders of the Muhammadiyah Youth Branch, Medan Belawan District. The results showed that the positive criminal law has regulated the form of prostitution, especially in Article 296 and Article 506 that the actions of prostitutes and users cannot be subject to criminal sanctions, only ensnare the brothel owner, pimps and brokers or brokers of prostitution. And the role of the Muhammadiyah youth organization in the Belawan branch has carried out these hidden prostitution prevention activities by holding various activities that are carried out regularly such as the presence of recitation, the existence of religious socialization activities by instilling religious, moral and ethical values, filled in by lecturers from the Medan Belawan branch of Muhammadiyah Organization. So that from these activities the hidden prostitution of boarding houses in Medan Belawan sub-district can be prevented and has been minimized